Effectiveness of a Scenario‐Based Simulation Training on Nursing Students' Learning Outcomes for Stoma Care: A Randomized Controlled Study - Fatih Dilek; Dilek Özden; Cahide Ayik (European Journal of Education, 2026)
ABSTRACT Simulation‐based learning is an effective teaching modality. However, there is a lack of evidence regarding scenario‐based simulation training with standardized patients on stoma care among nursing students. This study aimed to examine the effect of a scenario‐based hybrid simulation training using standardized patients and a wearable bud‐shaped stoma on nursing students' knowledge, skills, satisfaction, expectations, and opinions about stoma care. This randomized controlled study included 66 students, 33 in each group. Stoma care was practiced with a standardized patient who had a wearable bud‐shaped stoma stuck to the abdomen in the hybrid simulation group and a manikin in the control group. Study data were collected using the Stoma Care Skills Evaluation Form to measure students' skills, a questionnaire to reveal their knowledge and opinions, and the Student Satisfaction and Self‐Confidence in Learning Scale to find out about their satisfaction. Students' knowledge and opinion levels in both groups increased statistically significantly following the intervention ( p < 0.05). The students in the hybrid simulation group had higher skill ( p < 0.001) and satisfaction levels ( p = 0.043) than the control group. Scenario‐based hybrid simulation training increased students' knowledge, skills, expectations, and opinions about stoma care. It should be considered implementation and dissemination in health education.